NANOEMULSIFICATION OF BROMELAIN AND ITS FORMULATION INTO GEL PREPARATION TO IMPROVE EFFICACY ON A WOUND HEALING AGENT - Sulastri, Evi
Background and Objectives: Bromelain is a mixture of proteolytic enzymes presence in the fruit and stem of pineapple (Ananas comosus (Linn.) Merr.). It is known for clinical use as debridement for burn treatment. However, it is easily degraded by light, temperature and pH. Nanoemulsion of bromelain is promising to increase its stability. In this study, we investigated the nanoemulsion of bromelain and its formulation into gel preparation in order to increase its efficacy for the burns treatment. Bromelain acts as an enzymatic debridement. Method: Spontaneous or selfnanoemulsifying was applied in nanoemulsion of bromelain (NEB). Bromelain was incorporated various oil phases: virgin coconut oil (VCO), olive oil, vitamin E acetate and combination of both vitamin E acetate and VCO. As a surfactant, cremophor RH 40 was used together with polyethyleneglycol 400 as a cosurfactant. The stability of NEB in different oil phase was evaluated including particle size, polidispersity index, zeta potential, enzyme activity and nanoemulsion morphology. Furthermore, the most stable NEB was incorporated into matrik gel consisting of either sodium alginate or carboxymethyl chitosan (KMK). An in vivo evaluation was carried out by applying the NEB, the nanoemulsion bromelain-alginat gel (GANB), the nanoemulsion bromelain-KMK gel (GKNB), the natrium alginate gel bases (without NEB), the KMK gel base (without NEB) on rabbit burned skin. As a control we used untreated rabbit burned skin. The efficacy of NEB was evaluated by observing wound contraction, eschar, erythema, pus and edema score. Results: After 14 days of storage, NEB in vitamin E asetat as a oil phase was the most stable NEB among others. This formulation had a clear visual appearance, globul diameter of 74,37 nm, polidisversity index of 0,275, loading efficiency of 97,96 %, enzyme activity to the caseine was 1,350 unit/mL and zeta potential of - 2,49. Moreover the nanoemulsion bromelain showed the greatest reduction in wound contraction until the 14 th day of observation. The decline was statistically significant (p<0.05) compared to the other formula. Conclusion: Nanoemulsion of bromelain improved the stability of bromelain and showing better activity to heal third degree burns skin on animal model.